2016
DOI: 10.1111/gcb.13170
|View full text |Cite
|
Sign up to set email alerts
|

Do trace metals select for darker birds in urban areas? An experimental exposure to lead and zinc

Abstract: Trace metals from anthropogenic activities are involved in numerous health impairments and may therefore select for detoxification mechanisms or a higher tolerance. Melanin, responsible for the black and red colourations of teguments, plays a role in metal ion chelation and its synthesis is positively linked to immunity, antioxidant capacity and stress resistance due to pleiotropic effects. Therefore, we expected darker birds to (1) store higher amounts of metals in their feathers, (2) maintain lower metal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 82 publications
0
57
1
Order By: Relevance
“…Several previous studies have shown that the bioaccumulation of various macrominerals and microminerals, in particular Ca, increases with the intensity of pigmentation (derived from various porphyrin and melanin pigments) of avian feathers (Niecke et al 1999, Chatelain et al 2016 and of human hair and skin (reviewed in McGraw 2003). It is therefore assumed that reservoirs of melanin pigments serve as a sink for potentially harmful transition metal ions, adsorbing and harboring the very minerals that helped produce them and thereby offering chemoprotection to adjacent cells and tissues (Larsson 1993, McGraw 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have shown that the bioaccumulation of various macrominerals and microminerals, in particular Ca, increases with the intensity of pigmentation (derived from various porphyrin and melanin pigments) of avian feathers (Niecke et al 1999, Chatelain et al 2016 and of human hair and skin (reviewed in McGraw 2003). It is therefore assumed that reservoirs of melanin pigments serve as a sink for potentially harmful transition metal ions, adsorbing and harboring the very minerals that helped produce them and thereby offering chemoprotection to adjacent cells and tissues (Larsson 1993, McGraw 2003.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that highly melanic birds should be favored in an environment with a high level of certain metals (Chatelain et al., 2014). Many birds which adapt to live in European urban areas have melanin‐based plumage coloration (Chatelain et al., 2016). Yet, the mechanism and effect of toxic metals deposition are significantly understudied.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated levels of toxic compounds were also found in melanized feather parts. Regarding analysis of average effect size for lead, only one of the studies (Chatelain et al, 2016) showed a statistically significant relationship. The remaining studies provided no unambiguous results, probably due to a small sample size.…”
Section: Melanin Colorationmentioning
confidence: 93%
See 1 more Smart Citation
“…Lead exposure decreases bird immunity (unpubl.) and reproductive success (but there is no effect of metal exposure on bird breeding success; Chatelain et al 2015). Lead, by decreasing bird condition, may affect bird ability to preen, a costly behaviour that helps to regulate feather microbiota (Piault et al 2008, Moreno-Rueda 2010, Leclaire et al 2014b).…”
Section: Statistical Analysesmentioning
confidence: 99%